Life in search of readers : reading (in) Chicano/a literature - Martín-Rodríguez, Manuel M. (University of New Mexico Press, 2003)
In this examination of Chicano/a literature, Manuel M. Martín-Rodríguez analyzes the ways it connects with and is shaped by the interaction with its audiences.